Association of Placental Pathologic Findings with the Severity of Necrotizing Enterocolitis in Preterm infants – A Matched Case-Control Study. (4th March 2023) - Garg, Parvesh Mohan; Paschal, Jaslyn L.; Ansari, Md Abu Yusuf; Billington, Lauren; Ware, Jennifer; Adams, Kristin; Hamda, Youssef Al; Oshunbade, Adebamike; Rosenfeld, Charles R.; Mir, Imran N.
Abstract: Objective: To determine the association of placental pathology with the severity of necrotizing enterocolitis (NEC) in preterm infants. Methods: This single-center matched case-control study included infants with NEC ( n  = 107) and gestational age and birth weight-matched controls ( n  = 130), born between 2013 and 2020. Placentas were evaluated according to the Amsterdam Placental Workshop Group Consensus Statement. Results: Acute histologic chorioamnionitis with the fetal response was significantly more common in infants with surgical NEC vs. medical NEC (35.4% vs. 15.3%; p  = 0.02). On regression model, infants with multiple placental pathologies (OR 2.16; 95% CI 1.01 − 4.73; p  = 0.04) and maternal vascular malperfusion (OR 2.2; 95% CI 1.12 − 4.51; p  = 0.02) had higher odds of either medical or surgical NEC than controls. Conclusion: Infants with multiple placental lesions, including placental inflammatory and vascular lesions, were at higher risk of medical or surgical NEC in the postnatal period.